Laporan Kasus: Pasien Perempuan 39 Tahun dengan Thypoid Fever dan Dengue Fever - Juandi Rizki Ilhami; Nazaruddin Nazaruddin (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2026)
Typhoid fever is a febrile illness that commonly occurs in urban areas with poor sanitation. It is usually caused by the consumption of untreated water and contaminated food. Because the S. typhi bacterium can survive in water for days, contamination of surface water—such as wastewater, freshwater, and groundwater—serves as the primary cause of typhoid fever. The patient presented to the Emergency Department of Cut Meutia General Hospital with complaints of high fever for approximately 4 days prior to admission, which had worsened over the past 2 days. The fever fluctuated and was accompanied by chills. It worsened at night and was not influenced by weather or temperature. These symptoms were accompanied by vomiting every time the patient tried to eat, nausea, abdominal pain, headache, and weakness. The patient reported vomiting the contents of their meal every time they ate, leading to a loss of appetite. These symptoms began when the patient first developed a fever. The patient also experienced abdominal pain. Spontaneous bleeding was denied. On physical examination, the patient appeared weak but was alert and oriented. On neck examination, palpable enlargement of the thyroid glands was found on the right and left sides of the neck, measuring 2x2 cm, mobile, and soft. On abdominal examination, increased bowel sounds were noted. Vital signs were normal except for the patient’s febrile temperature. Laboratory tests revealed a Tubex blood test result of scale 4 and a positive dengue IgG serology result.